A novel multi-class classification model for schizophrenia, bipolar disorder and healthy controls using comprehensive transcriptomic data - Yang, Qingxia; Li, Yi; Li, Bo; Gong, Yaguo (Computers in biology and medicine, 2022)
Two common psychiatric disorders, schizophrenia (SCZ) and bipolar disorder (BP), confer lifelong disability and collectively affect 2% of the world population. Because the diagnosis of psychiatry is based only on symptoms, developing more effective methods for the diagnosis of psychiatric disorders is a major international public health priority. Furthermore, SCZ and BP overlap considerably in terms of symptoms and risk genes. Therefore, the clarity of the underlying etiology and pathology remains lacking for these two disorders. Although many studies have been conducted, a classification model with higher accuracy and consistency was found to still be necessary for accurate diagnoses of SCZ and BP. In this study, a comprehensive dataset was combined from five independent transcriptomic studies. This dataset comprised 120 patients with SCZ, 101 patients with BP, and 149 healthy subjects. The partial least squares discriminant analysis (PLS-DA) method was applied to identify the gene signature among multiple groups, and 341 differentially expressed genes (DEGs) were identified. Then, the disease relevance of these DEGs was systematically performed, including (α) the great disease relevance of the identified signature, (β) the hub genes of the protein-protein interaction network playing a key role in psychiatric disorders, and (γ) gene ontology terms and enriched pathways playing a key role in psychiatric disorders. Finally, a popular multi-class classifier, support vector machine (SVM), was applied to construct a novel multi-class classification model using the identified signature for SCZ and BP. Using the independent test sets, the classification capacity of this multi-class model was assessed, which showed this model had a strong classification ability. [Display omitted] •The gene signature of SCZ, BP, and healthy subjects was identified by the PLS-DA using comprehensive transcriptomic data.•The disease relevance of gene signature, hub genes of the PPI network, GO terms, and pathways was systematically performed.•A novel classification model of SCZ, BP, and healthy subjects was constructed by the SVM using the identified gene signature.•The strong capacity of the multi-class classification model for SCZ and BP was validated based on the independent test set.